2018
DOI: 10.1111/jfbc.12629
|View full text |Cite
|
Sign up to set email alerts
|

Role of food-derived opioid peptides in the central nervous and gastrointestinal systems

Abstract: Opioid receptors are widely distributed in central nervous system and peripheral tissues. Endogenous opioid receptor ligands are involved in many physiological processes.Exogenous peptides, derived from food proteins with gastrointestinal proteases, also exert opioid-like activities, and they include gluten exorphins (wheat), casomorphins (milk), rubiscolins (spinach), and soymorphins (soybean). Milk-derived opioid peptides play both agonistic and antagonistic roles, and most of the opioid peptides exert regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Finally, it is interesting to note that a range of both endogenous (e.g., amphibian opioid peptides such as dermorphins and deltorphins) and food-derived (e.g., derivatives from milk and soya such as soymorphines and β-casomorphins) opioid peptides, possessing low levels of potency (Teschemacher et al, 1997;Negri et al, 2000;Ohinata et al, 2007;Liu and Udenigwe, 2018), were not mentioned in psychonaut fora.…”
Section: Miscellaneous: Non-fentanyl Compounds Prescribing Opioids mentioning
confidence: 99%
“…Finally, it is interesting to note that a range of both endogenous (e.g., amphibian opioid peptides such as dermorphins and deltorphins) and food-derived (e.g., derivatives from milk and soya such as soymorphines and β-casomorphins) opioid peptides, possessing low levels of potency (Teschemacher et al, 1997;Negri et al, 2000;Ohinata et al, 2007;Liu and Udenigwe, 2018), were not mentioned in psychonaut fora.…”
Section: Miscellaneous: Non-fentanyl Compounds Prescribing Opioids mentioning
confidence: 99%
“…38 Moreover, foodderived opioid peptides may be involved in the regulation of inflammatory processes. 39 Intestinal Mu opioid receptors are well described as responding to peptides in their opioid function and a variety of other functionalities including hormonelike, analgesia, and anti-hypertensive effects. 40 Peptides from bovine, casein and soy protein were characterized for their functionality.…”
Section: Early Clinical Observationsmentioning
confidence: 99%
“…Studies have revealed that opioid peptides derived from animal proteins bind to µ‐opioid peptide receptors and those obtained from plant proteins bind to δ‐opioid peptide receptors (Yoshikawa et al., 2005), except for soymorphins that bind to µ‐opioid peptide receptors, due to their nature of receptor selectivity (Liu & Udenigwe, 2019; Ohinata et al., 2007). Various studies showed that opioid peptides could be isolated from milk (Fan et al., 2019; Hafeez et al., 2014), yogurt (Papadimitriou et al., 2007), kefir (Ebner et al., 2015), cheese (Nguyen et al., 2015), whey (Pihlanto‐Leppälä, 2000; Yadav et al., 2015), wheat (Garg et al., 2018), amaranth grain (Tovar‐Pérez et al., 2019), soybean (Liu & Udenigwe, 2019), meat (Udenigwe & Howard, 2013), and fish and shellfish (Harnedy & FitzGerald, 2012). It has been shown that these food‐derived exogenous opioid peptides could exert agonistic activity that is comparable to that of endogenous ligands, whereas the antagonistic peptides could exert inhibitory effects similar to naloxone, a potent drug that has antagonistic effect on opiate receptor (Hartmann & Meisel, 2007).…”
Section: Structure–activity Relationship Of Bpsmentioning
confidence: 99%